The Bat Signal: Exploring the Relationship Between Justice and Design - Bryan Bell (Oz, 2006)
SEED is a network of organizations and individuals dedicated to build and support a culture of civic responsibility and engagement in the built environment and the public realm. We promote and foster public interest architecture, urbanism, and landscapes, which are design and socially progressive, celebrating the idea that design matters and all people can shape their world.